By activating endothelium histone H4 mediates oleic acid-induced acute respiratory distress syndrome - Yanlin Zhang; Jingjin Tan; Yiran Zhao; Li Guan; Shuqiang Li (BMC Pulmonary Medicine)
Abstract Objective This study investigated pathogenic role and mechanism of extracellular histone H4 during oleic acid (OA)-induced acute respiratory distress syndrome (ARDS). Methods: ARDS was induced by intravenous injection of OA in mice, and evaluated by blood gas, pathological analysis, lung edema, and survival rate. Heparan sulfate (HS) degradation was evaluated using immunofluorescence and flow cytometry. The released von Willebrand factor (vWF) was measured using ELISA. P-selectin translocation and neutrophil infiltration were measured via immunohistochemical analysis. Changes in VE-cadherin were measured by western blot. Blocking antibodies against TLRs were used to investigate the signaling pathway. Results: Histone H4 in plasma and BALF increased significantly after OA injection. Histone H4 was closely correlated with the OA dose, which determined the ARDS severity. Pretreatment with histone H4 further aggravated pulmonary edema and death rate, while anti-H4 antibody exerted obvious protective effects. Histone H4 directly activated the endothelia. Endothelial activation was evidently manifested as HS degradation, release of vWF, P-selectin translocation, and VE-Cadherin reduction. The synergistic stimulus of activated endothelia was required for effective neutrophil activation by histone H4. Both TLRs and calcium mediated histone H4-induced endothelial activation. Conclusions: Histone H4 is a pro-inflammatory and pro-thrombotic molecule in OA-induced ARDS in mice.